Development of CTL Approach Learning Tools to Improve Critical Thinking Skills and Science Learning Outcomes of Class V Primary School Students - Siswanto, Gandi; Sunardi, Sunardi; Sulistyowati, Lilik (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
The background to this research is that the learning methods used by teachers are still conventional, there is a lack of students' critical thinking skills so that students' learning outcomes decrease and there is a need for education that supports 21st-century learning as well as previous research that is reviewed and refined. This research aims to improve critical thinking skills and learning outcomes of class V students in science subjects at SDN Jatiroto 03. This research uses the development of learning tools which include LKPD, learning results tests, lesson plans, and teaching materials. Teaching materials and LKPD make it easier for students to understand food webs. The learning outcomes test questions contain HOTS (Higher Other Thinks Skill) questions which aim to increase student learning outcomes scores. The method used in this research is development or Research and Development based on the Four D Model with the development model consisting of four development stages, namely defining, planning, developing, and disseminating. The data collection procedures used are data collection procedures for CTL, observation to measure critical thinking skills, learning outcomes in the form of tests, and data collection processes for LKPD products and teaching materials. The data analysis method used is instrument testing, testing learning outcomes test questions, testing LKPD products and teaching materials. The results of this research show that the learning tools developed according to expectations meet the criteria for validity, practicality, and effectiveness so that learning tools using the CTL approach to improve critical thinking skills and student learning outcomes are suitable for use in science learning for fifth-grade elementary school.